2014
DOI: 10.3892/ol.2014.2633
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of HIC-1 gene by saRNA inhibits clonogenicity and invasiveness in breast cancer cells

Abstract: Hypermethylated in cancer 1 (HIC-1) is a tumor suppressor gene, which is epigenetically silenced in breast cancer. It is known that the loss of HIC-1, caused by promoter hypermethylation, is associated with tumor aggression and poor survival in breast carcinoma. It has been shown that small activating RNA (saRNA) targeting promoter sequences may induce gene re-expression. In the current study, saRNA was used to restore HIC-1 expression, and the effects on colony formation, invasiveness and the cell cycle in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…ERBB2 is located in chromosome 17q21.2, where some common oncogenes or tumor suppressor genes, such as TOP2A, TAU, p53, and HIC-1 are located ( Zhang and Yu, 2011 ). Our previous studies confirmed that re-activation of tumor suppressor HIC-1 by small-activating RNAs inhibits cell division, growth and invasion ( Zhao et al, 2014 , 2015 ). Retinoic acid receptor alpha (RARA) is another gene located on chromosome 17q21.2.…”
Section: Introductionsupporting
confidence: 82%
“…ERBB2 is located in chromosome 17q21.2, where some common oncogenes or tumor suppressor genes, such as TOP2A, TAU, p53, and HIC-1 are located ( Zhang and Yu, 2011 ). Our previous studies confirmed that re-activation of tumor suppressor HIC-1 by small-activating RNAs inhibits cell division, growth and invasion ( Zhao et al, 2014 , 2015 ). Retinoic acid receptor alpha (RARA) is another gene located on chromosome 17q21.2.…”
Section: Introductionsupporting
confidence: 82%
“…Although studies have identified HIC-1 as having frequent changes in hypermethylation or loss of heterozygosity in many human cancers [ 40 , 41 ], the molecular mechanisms through which HIC-1 inhibits cancer progression remain poorly understood. HIC-1 is a multifunctional, sequence-specific transcriptional repressor that interacts with several major repression and chromatin remodeling complexes [ 42 , 43 ]. To date, many studies have showed that the IL-6/Janus kinase/STAT3 signaling pathways are involved in drug resistance, angiogenesis, migration, and other processes in cancers [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%